Impaired Expression of Focal Adhesion Kinase in Mesenchymal Stromal Cells from Low-Risk Myelodysplastic Syndrome Patients - Wu, Yuenv; Aanei, Carmen Mariana; Kesr, Sanae; Picot, Tiphanie; Guyotat, Denis; Campos Catafal, Lydia (Frontiers in Oncology, 2017)
The pathogenic role of mesenchymal stromal cells (MSC) in myelodysplastic syndromes (MDS) development and progression has been suggested by numerous studies, yet it remains controversial in some aspects1,2. In the present study, we found distinct features of MSCs from low risk (LR)-MDS stromal microenvironment as compared to those from healthy subjects. At the molecular level, focal adhesion kinase (FAK), a key tyrosine kinase in control of cell proliferation, survival and adhesion process was found profoundly suppressed in expression and activation in LR-MDS MSC. At functional level, LR-MDS MSCs showed impaired growth and clonogenic capacity which were independent of cellular senescence and apoptosis. The pro-adipogenic differentiation and attenuated osteogenic capacity along with reduced SDF-1 expression could be involved in creating an unfavorable microenvironment for hematopoiesis. In conclusion, our experiments support the theory that the stromal microenvironment is fundamentally altered in LR-MDS and these preliminary data offer a new perspective in LR-MDS pathophysiology.